2020
DOI: 10.1088/2515-7647/ab7080
|View full text |Cite
|
Sign up to set email alerts
|

Defect-free laser powder bed fusion of Ti–48Al–2Cr–2Nb with a high temperature inductive preheating system

Abstract: In the industrial panorama, laser powder bed fusion (LPBF) systems enable the near net shaping of metal powders into complex geometries with unique design features. This makes the technology appealing for many industrial applications, which require high performance materials combined with lightweight design, lattice structures and organic forms. However, many of the alloys that would be ideal for the realisation of these functional components are classified as difficult to weld due to their cracking sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…A conceptual design of a new pre-heating system (Fig. 3) for the LPBF technology was recently experimented with by Caprio et al [27]. With the novel design, the authors were able to maintain the preheating temperature of the base plate and the previously Fig.…”
Section: Encouraging Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A conceptual design of a new pre-heating system (Fig. 3) for the LPBF technology was recently experimented with by Caprio et al [27]. With the novel design, the authors were able to maintain the preheating temperature of the base plate and the previously Fig.…”
Section: Encouraging Resultsmentioning
confidence: 99%
“…The keyhole effect phenomenon occurs because of excessive energy absorption into the powder bed [46]. Despite the presence of the pores in the TiAl samples the current approach of maintaining a high preheating temperature throughout the manufacturing process as proposed by Caprio [27], have demonstrated that the goal of manufacturing the crack-free TiAl components via LPBF is becoming a reality. The next step is how to produce the crack-free samples without pores.…”
Section: Encouraging Resultsmentioning
confidence: 99%
See 3 more Smart Citations